The Role of social media (Tourist Visit of Arab-Palembang Village in Pandemic Period) - Erdiansyah Erdiansyah; Ahmad Maulana; Edduar Hendri (LAFADZ JAYA Publisher, 2023)
This study was conducted to describe the role of social media in optimizing Arab-Palembang village tourist visits during the pandemic. The method used in this study is a mixed method, which combines qualitative and quantitative methods. To collect research data, questionnaires, observation, interviews and documentation techniques were used. The results achieved from this research are that social media has a positive role in optimizing Arab-Palembang village tourist visits during the pandemic. As indicators of social media used, namely social media as a means of information, which is persuasive and becomes entertainment for the community.